Preventing violent radicalization of youth through dialogic evidence-based policies. (July 2018) - Aiello, Emilia; Puigvert, Lídia; Schubert, Tinka
Radicalization of youth leading to violent extremism in the form of terrorism is an urgent problem considering the rise of young people joining extremist groups of different ideologies. Previous research on the impact of counter-terrorism polices has highlighted negative outcomes such as stigmatizing minority groups. Drawing on qualitative research conducted under the PROTON project (2016–2019) by CREA-UB on the social and ethical impact of counter-terrorism policies in six EU countries, the present article presents and discusses the ways in which actions characterized by creating spaces for dialogue at the grassroots level are contributing to prevent youth violent radicalization. The results highlight four core elements underlying these spaces for dialogue: providing guidance to be safe in the exploration of extremist messages and violent radicalization; the rejection of violence; that dialogue is egalitarian; and that relationships are built on trust so that adolescents and young adults feel confident to raise their doubts. If taken into account, these elements can serve to elaborate dialogic evidence-based policies . The policies which include a dialogue between the scientific evidence and the people affected by them once implemented, achieve positive social impact.